If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(8x + -7) = -4 + -4x Reorder the terms: -8(-7 + 8x) = -4 + -4x (-7 * -8 + 8x * -8) = -4 + -4x (56 + -64x) = -4 + -4x Solving 56 + -64x = -4 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 56 + -64x + 4x = -4 + -4x + 4x Combine like terms: -64x + 4x = -60x 56 + -60x = -4 + -4x + 4x Combine like terms: -4x + 4x = 0 56 + -60x = -4 + 0 56 + -60x = -4 Add '-56' to each side of the equation. 56 + -56 + -60x = -4 + -56 Combine like terms: 56 + -56 = 0 0 + -60x = -4 + -56 -60x = -4 + -56 Combine like terms: -4 + -56 = -60 -60x = -60 Divide each side by '-60'. x = 1 Simplifying x = 1
| sigmax+1= | | -34+6x=-4(-4x-2)-4x | | -2cos^2x+cosx+1=0 | | 6.6n+7.5=19.8 | | (3x+2)(2x+5)=0 | | 8+6(6n-7)=-8n+10 | | 3.8n+3.9=19.4 | | 4v^2-21v-18= | | ex+1= | | -6n+19=1-4(3n+6) | | 9+7z-16=13z-7-6z | | 6+8z-11=15z-5-7z | | -8u^2+10u-3= | | 14.95+0.13x=-15.00+0.39 | | a(ba)= | | z^2=3+4i | | 16t^2+32x+48=0 | | -16+9y^2=0 | | -9q+15+12q=3(q+3)-5 | | (5x^2)-10x+20=0 | | 14.95+0.15x=-15.00+0.39x | | -6q+11+10q=4(q+2)-7 | | 1.735t^2+58.9t-500=0 | | -8y-1=-7y-5 | | t(23)=t(23)-2 | | x^4-3x^3+2x^2-4x-8=0 | | -6p+11+10P=4(P+2)-7 | | 4-w=9 | | 4(4x+3)=7(x-5)-9 | | 3x-2=21x+4 | | 2x+13=8x+31 | | 64x=124 |